Peripapillary Halo in Inflammatory Papillitis of Birdshot Chorioretinopathy - Khodeiry MM (Dove Medical Press, 2021)
Mohamed M Khodeiry,1,2 Xiangxiang Liu,1,3 Mohamed S Sayed,1 Raquel Goldhardt,1 Giovanni Gregori,1 Thomas A Albini,1 Richard K Lee1 1Bascom Palmer Eye Institute, Department of Ophthalmology, University of Miami Miller School of Medicine, Miami, FL, 33136, USA; 2Research Institute of Ophthalmology, Department of Ophthalmology, Giza, 12557, Egypt; 3Beijing Eye Institute, Beijing Tongren Eye Center, Beijing Tongren Eye Hospital, Capital Medical University, Beijing, 100730, People’s Republic of ChinaCorrespondence: Richard K LeeBascom Palmer Eye Institute, Department of Ophthalmology, University of Miami Miller School of Medicine, 900 NW 17 th Street, Miami, FL 33136, USATel +1 305 326-6400Fax +1 305 547-3658Email rlee@med.miami.eduPurpose: Peripapillary halos (PPH) are peripapillary changes observed surrounding the optic nerve head in normal eyes and eyes with different disorders. Recognizing the microstructure and mechanism of development of these halos will help clinicians understand the different associated retinal and optic nerve head pathologies. We describe the in vivo histological characteristics of PPH in birdshot chorioretinopathy (BSCR).Patients and Methods: This was a prospective observational case-series in a single tertiary referral center. Six eyes of three patients with PPH associated with BSCR were determined through clinical examination, fundus photography, and fundus autofluorescence (FAF). Patients underwent swept-source optical coherence tomography (SS-OCT) imaging of the optic nerve head and peripapillary region.Results: In SS-OCT B-scans across the area of PPH, we observed thinning and interruption of retinal pigment epithelium (RPE)-Bruch’s membrane complex. These halos are a circumferential form of alpha zone RPE-associated crescentic peripapillary atrophy (PPA), unlike the PPH observed with myopia and normal aging.Conclusion: PPH in BSCR patients may be a sign of prior inflammatory optic neuropathy.Keywords: birdshot chorioretinitis, optical coherence tomography, optic nerve head, peripapillary halo, peripapillary atrophy